Entrepreneurship as a socio-cultural phenomenon: historical and philosophical reconstruction - Barsuk, Irina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with historical and philosophical reconstruction of the phenomenon of entrepreneurship in the context of the genesis, conceptual prerequisites of development and the disciplinary organization of economic knowledge. Interest to this phenomenon is due to the immense amount of its interpretations not only in economic literature, but also in various areas of socio-humanitarian knowledge. This accentuates its multidisciplinary nature and important role in the social dynamics of post-industrial societies. It is proved that classical entrepreneurship is a unique resource that allows activity in periods of economic downturn, influencing the competitive environment, developing the infrastructure of the economy, quickly responding to consumer demand, generating and introducing innovative ideas.
Keywords: entrepreneur; entrepreneurship; profit; risk; uncertainty; innovation; arbitrage transactions; management